2019
DOI: 10.1016/j.aquatox.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Harmful or harmless: Biological effects of marennine on marine organisms

Abstract: Highlights ► The biological effects of marennine were studied on different marine organisms. ► Marennine is the blue water-soluble pigment produced by the diatom Haslea ostrearia. ► Blooms of blue Haslea are recorded worldwide. ► Marine organisms can be exposed to significant amount of marennine during blooms.► Marennine significantly affects early developmental stages of the tested organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, previous studies conducted with purified extracellular marennine (EMn) on marine bacteria, including Vibrio species, confirmed that the pigment itself did exert an antibacterial activity [9,10,11,12]. Moreover, a recent study has demonstrated the biological activities of marennine solutions, including BW and EMn, on the development or survival of various marine organisms, and comparable effects were observed between the different solutions tested [21]. Also, if blue Haslea species should be cultured at large scale to ensure the production of marennine solutions for applications as antimicrobials in aquaculture, BW represents the easiest and cheapest production process, compared to the purified pigment.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies conducted with purified extracellular marennine (EMn) on marine bacteria, including Vibrio species, confirmed that the pigment itself did exert an antibacterial activity [9,10,11,12]. Moreover, a recent study has demonstrated the biological activities of marennine solutions, including BW and EMn, on the development or survival of various marine organisms, and comparable effects were observed between the different solutions tested [21]. Also, if blue Haslea species should be cultured at large scale to ensure the production of marennine solutions for applications as antimicrobials in aquaculture, BW represents the easiest and cheapest production process, compared to the purified pigment.…”
Section: Discussionmentioning
confidence: 99%
“…Marennine is responsible for the greening of oyster gills in Western Europe [4][5][6][7]. Marennine and marennine-like pigments also display several biological activities (e.g., antibacterial, antiviral, or antioxidant) qualifying them for putative use in aquaculture and biotechnology [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The name “marennine” was proposed by Lankester [ 19 ] in reference to Marennes-Oléron (Marennes, 45°49′25.8″ N 1°06′16.3″ W), a region of western France where oysters have been farmed for centuries. This pigment is responsible for the greening of oyster gills, a natural phenomenon of great importance for the oyster industry [ 20 ]. Haslea ostrearia is not only present on the French Brittany coasts but also within the Pacific Ocean on the Australian, American and Japanese coasts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%